Method for Screening and MALDI-TOF MS Sequencing of Encoded Combinatorial Libraries - Hu, Bi-Huang (2007)
We describe a new method for encoded synthesis, efficient on-resin screening, and rapid unambiguous sequencing of combinatorial peptide libraries. An improved binary tag system for encoding peptide libraries during synthesis was designed to facilitate unequivocal assignment of isobaric residues by MALDI-TOF MS analysis. The improved method for encoded library synthesis was combined with a new versatile on-resin screening strategy that permitted multiple stages and types of screening to be employed successively on one library under mild conditions. The new method facilitated a combinatorial study of transglutaminase (TGase) enzyme substrate peptides, revealing new details of the effect of amino acid composition on TGase substrates. The approach was first demonstrated for an encoded library (130 321 compounds) of lysine pentapeptide substrates of TGase, synthesized using the “split-mix” method. The library was reacted on-resin with TGase enzyme and a soluble desthiobiotin labeled glutamine substrate. Initial screening was performed by adsorbing streptavidin-coated magnetic microparticles onto library beads, followed by magnetic separation. The differential binding affinities of desthiobiotin and biotin for streptavidin were exploited to release the magnetic microparticles and regenerate the desthiobiotin-labeled resin beads for further screening by flow-cytometry-based automated bead sorting, resulting in 345 beads that were sequenced by MALDI-TOF MS analysis. A second library consisted of encoded glutamine hexapeptide substrates, which was reacted on-resin with TGase enzyme and a soluble desthiobiotin-labeled cadaverine. Two-stage screening identified 267 glutamine peptides as TGase-reactive, of which 21 were further analyzed by solution-phase enzyme kinetics. Kinetic results indicated that the peptide PQQQYV from the library has a 68-fold greater substrate specificity than the best known glutamine substrate QQIV. The new encoding and screening strategies described here are expected to be broadly applicable to synthesis and screening of combinatorial peptide libraries in the future.